Factors affecting economic profits of Phon Yang Kham beef cattle farming in Sakon Nakhon province - P. Chaisombut; H. Umpapol; R. Hanmontree; P. Hanmontree; C. Srilapat; P. Sawnongbua; C. Chaisitipatana; L. Lertjunthuk; N. Rapankum (Diponegoro University, 2022)
The study aimed to determine factors affecting economic profits of beef cattle business in Sakon Nakhon Province. A sample of 400 members of Kor Ror Por Klang Phon Yang Kham Livestock Coop-erative Limited was determined by using Taro Yamane method, and binary logistic regression analysis was used to analyze the data. The findings showed that the variables with the statistical significance of 0.01 included concentrate feeds, roughage, and the raised period of less than or equal to 12 months. They were statistically significant at 0.001 0.000, and 0.000 respectively, and the odd ratios were 1.387, 0.921, and 5.697 respectively. Additionally, the variables with the statistical significance of 0.05 includ-ed Charolais cattle (62.50%) and farm location. The two variables were statistically significant at 0.023 and 0.039 respectively with the odd ratios of 5.083 and 0.595 respectively. If the cows are fed on 1 more kg/day of more concentrated feed, it is likely for the farmers to increase economic profit by 0.921 times and 1.387 times respectively. The probability of economic profit is by 5.697 times if the cattle are raised no more than 12 months. The cross-bred cattle with 62.50% Charolais breed showed the proba-bility for the farmers to gain economic profit by 5.083 times. Finally, those who had farms located next to the farm family’s home were more likely to gain less economic profit by 0.595 times.